Effectiveness of Brief Psychodynamic Therapy With Children and Adolescents: An Outcome Study - Gatta, Michela; Miscioscia, Marina; Svanellini, Lorenza; Spoto, Andrea; Difronzo, Manuela; de Sauma, Maxim; Ferruzza, Emilia (Frontiers in Pediatrics, 2019)
Studies on psychotherapy with children and adolescents provided by the Italian Public Mental Health Service appear to be lacking so far, while the scientific community has focused more on the value of cognitive-behavioral psychotherapeutic approaches. This paper examines the effects of one-year psychodynamically-oriented interventions with children and adolescents aged between 6 and 18 years (M=12.08, SD=3.7), and their parents, conducted at a Developmental Neuropsychiatry Service (SCIAF) forming part of the Italian National Health Service. After a psychodiagnostic assessment, two types of therapeutic intervention were offered: children and adolescents allocated to Group 1 (N=26) were offered individual psychodynamic psychotherapy alone, while those in Group 2 (N=31) were offered a treatment combining individual therapy for the child/adolescent with therapy for the parental couple. This study examines the effects of this time-limited (12-month) psychodynamically-oriented psychotherapy in terms of improvements in patients’ symptoms (measured with the CBCL and YSR 11-18), and parents’ perception of family empowerment (measured with the FES scale). Our findings seem to be in line with published reports of poor parenting behavior (low warmth, harsh discipline, poor monitoring, and negative parenting) being positively associated with Externalizing problems in childhood. Our psychotherapy achieved positive outcomes for both ‘Internalizing’ and ‘Externalizing’ problems, considering age-related differences, ICD-10 (2004) diagnoses, and the types of treatment offered. No statistically significant changes were seen in the parents’ perceptions of empowerment at 12 months.